PENERAPAN KAIDAH AL-TAFSIR BI AL-MA’TSUR DALAM TAFSIR AL-TABARI - Aminsyah Suhada; Ali Akbar; Hidayatullah Ismail; Rahmat IR Limbong (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2026)
This research discusses applying the rules of al-tafsir bi al-ma'tsur in interpreting al-tabari. Mufassir who uses this approach considers that this approach is more accurate in interpreting the Qur'an because it is based on Naqli arguments as the main source. This research uses the library research method by using all written works as reference material. The result of this research is to apply the rules of tafsir bi al-Ma'tsur to the book of tafsir al-Tabari such as al-Tabari interpreting Q.S al-Baqarah verse 40 with Q.S al-'A'raf verse 31, likewise when al-Tabari interprets Q.S al -Fatihah verse 7 on the word